Comprehensive model of thermal phenomena and phase transformations in laser welding process. (August 2016) - Kubiak, M.; Piekarska, W.
Highlights: Prediction of fusion zone and heat affected zone geometry in laser welding process. Estimation of structural composition of the laser welded joint. Considering austenitization temperatures changing with heating rates. Determining the impact of latent heats on the temperature field. Comparison of predicted characteristic zones of joints with experimental results. Abstract: This paper concerns computational modelling of thermal phenomena and phase transformations in solid state in laser welding process. The analysis is performed on the basis of numerical solution into continuum mechanics governing equations as well as classic Johnson–Mehl–Avrami (JMA) and Koistinen–Marburger (KM) kinetics models with continuous heating transformation (CHT) and continuous cooling transformation (CCT) diagrams of S460 steel. The influence of latent heats on temperature distributions is analysed. Obtained results include temperature field, melted material velocity field in the fusion zone and structure composition of welded joint. Calculations are partially verified by experimental data.